Usability requirements for buildings: a case study on primary schools. - Soares, Marcelo M.; Jacobs, Karen; Duca, Gabriella (Work)
This paper concerns an applied research aimed at applying the concept of usability, as derived form the standard ISO 9241/11, in the filed of building design, namely primary schools. Starting from the concept that space characteristics play a very relevant role in learning performances, the study presented here developed an original methodology for the assessment of effectiveness, efficiency and satisfaction of buildings hosting primary schools, in order to create a school environment better supporting users in their tasks. Research core is the framework of usability requirements and their related markers, indicators and technical specification that has been formulated in order to check compliance of urban area, building, rooms and architectural details with users needs. Therefore, a detailed task analysis of pupils and teacher tasks has been carried out and two questionnaires addressed to a significant users panel have been formulated for satisfaction survey. Lastly, a matrix for an overall reading of gathered data has been set-up and criteria for usability assessment based on that data has been defined. The whole study has been developed within the case study of a primary school in the Naples city centre, whose contents and results are discussed.